Differences in Perceptions of Organizational Fairness Based on Job Characteristics among Police Officers - Reynolds, Paul D. (American journal of criminal justice, 2018)
Profuse research supports that organizational work environments are linked to varying police officers’ work-related attitudes and behaviors. Yet, there remains a lack of information pertaining to how perceptions of organizational fairness may differ among police officers based on job characteristics. To help fill this void, this exploratory research examines differences in fairness perceptions based on officers’ tenure, rank, duty assignment, and department size with their perceptions of organizational fairness. To examine this relationship, an online survey of police officers ( n = 1649) in a southern state in the United States that were members of a police officer association was conducted. Findings support that differences in overall fairness perceptions exist for all the aforementioned job characteristics. This study furthers our knowledge and understanding of how job characteristics (e.g., tenure, rank, duty assignment, and department size) may be associated with police officers’ work-related attitudes.